1982
DOI: 10.1029/gl009i006p00613
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the aerosol and ice crystal populations in tropical stratospheric cumulonimbus anvils

Abstract: A pair of particle size spectrometers was flown aboard the NASA U‐2 operating from the Canal Zone to make measurements of the aerosol and ice crystal budgets in cirrus produced by thunderstorms in the tropics. Measurements indicate that fairly large crystals up to 1 mm in size are injected into the stratosphere during cumulonimbus activity. Ice water contents range from a few thousandths to a few hundredths of a gram per cubic meter. Because the ambient temperature is typically around −80°C the mass of the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 2 publications
0
24
1
Order By: Relevance
“…The amount of supercooled water there peaked at only about 10% adiabatic water, in contrast to the peak of 50% in west Texas (Rosenfeld and Woodley 2000) to the record measurement of nearly 100% adiabatic water in Argentina (this study), respectively. Cloud-physics jet aircraft have been used also to make measurements in thunderstorm anvils (Knollenberg et al 1982;Smith et al 1994;Lawson et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of supercooled water there peaked at only about 10% adiabatic water, in contrast to the peak of 50% in west Texas (Rosenfeld and Woodley 2000) to the record measurement of nearly 100% adiabatic water in Argentina (this study), respectively. Cloud-physics jet aircraft have been used also to make measurements in thunderstorm anvils (Knollenberg et al 1982;Smith et al 1994;Lawson et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Those measurements, made during the summer over Colorado, Wyoming and Minnesota, showed that the largest size of crystals was between 10 and 30 mm with concentrations as high as 1000 L (1 . In 1980, Knollenberg et al (1982) flew an optical array probe and a new single particle light scattering probe (Knollenberg, 1976) with a size range from approximately 2 to 50 mm on the NASA U-2 high-altitude aircraft over Panama, the first airborne cirrus measurements to be made in the tropics. All of the measurements were made in anvil cirrus with the highest number concentrations in the size range 10 and 50 mm, but the mass was mostly in crystals between 40 and 50 mm.…”
Section: Introductionmentioning
confidence: 99%
“…From this single measurement it is not possible to determine whether the smaller mode is the result of additional nucleation during the convective rise or of growth of the larger particles and evaporation of the smaller ones. Similar bimodality has appeared in some of the other observations as well [Knollenberg et al, 1982;Zhang et al, 1999], however, and we are presently undertaking a more thorough investigation of this aspect by means of modelling based on the meteorology.…”
Section: Resultsmentioning
confidence: 97%